Effect of emotional stress on cold structural and functional state dental pulp rats - I. G. Ostrovskaya; T. P. Vavilova; L. M. Erofeeva; A. V. Mitronin (Кубанский научный медицинский вестник)
In the experiment established the influence of emotional and cold stress not only on metabolic changes, but also structural changes in the dental pulp. It was shown that the dental pulp stress leads to disruption of intercellular interactions due to morphological characteristics and cell fusion proteins and peptides. Short-term stress exposure causes a reaction similar to the inflammation of the pulp and long leads to inhibition of calcium and phosphorus metabolism and apoptosis odontoblasts.